Ch2FCF3 Gas Flow Rate Effects of SiO2 Plasma Etching Rate on Quartz Crystal Microbalance - Antonius Prisma Jalu Permana; Dionysius Joseph Djoko HS; Masruroh Masruroh (Natural B, Journal of Health and Environmental Sciences, 2016)
Effect of gas flow rate on the surface of quartz crystal SiO2 during plasma etching was studied. The etching process was applied using the capacitively coupled plasma (CCP) reactor generated with 100 W power AC generator at low frequency of 40 kHz using a gas flow of CH2FCF3. The main objective of this study was to determine the effect of changing gas flow rate on the plasma etching rate on the SiO2 surfaces. Gas flow rate was varied between 20-40 mL/min, while keeping all other plasma parameters constant. The etched surface of SiO2 was analyzed using white-light profilometer (Topography Measurement System (TMS 1200 Micro Lab)). The results show the physical etching processes influenced the rate of etching at a low gas flow rate, while the higher flow rate influence reactive ion etching (RIE) in the etching process. The maximum etching rate is found at 7.753 nm / min achieved in plasma etching process.